Perbandingan Sanksi Pertanggungjawaban Pidana Perkosaan di Indonesia dan Singapura - Latifatul Mufidah Amalia; Aufa Mufidah Rahman (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2024)
This research discusses the comparison of sanctions for liability for the crime of rape between the Indonesian Criminal Code and Singapore's Penal Code 1871. In the Indonesian Criminal Code, rape is regulated in Article 473, while in the Singapore Penal Code, rape is regulated in Article 375. This research uses normative analysis and comparative analysis methods. The results of the research show that there are differences in sanctions for responsibility for the crime of rape between the Indonesian Criminal Code and the Singapore Penal Code. The Indonesian Criminal Code regulates criminal sanctions in the form of imprisonment for a maximum of 12 years and a maximum of 15 years if rape of a child or serious injury results, while the Singapore Penal Code regulates prison sanctions of 8 years to 20 years plus a minimum caning sentence of 12 lashes. This research also shows that there are differences in the definition of rape between the Indonesian Criminal Code and the Singapore Penal Code.